Analysis of Histone Modifications by Mass Spectrometry. (16th April 2018) - Völker‐Albert, Moritz Carl; Schmidt, Andreas; Forne, Ignasi; Imhof, Axel
Abstract: Histone N termini undergo diverse post‐translational modifications that significantly extend the information potential of the genetic code. Moreover, these modifications mark specific chromatin regions, modulating epigenetic control, lineage commitment, and overall function of chromosomes. It is widely accepted that histone modifications affect chromatin function, but the exact mechanisms by which modifications on histone tails and specific combinations of modifications are generated, and how they cross‐talk with one another, are still enigmatic. Mass spectrometry is the gold‐standard method for analyzing histone modifications, as it allows the quantification of modifications and combinations. This unit describes how high‐resolution mass spectrometry can be used to study histone post‐translational modifications. © 2018 by John Wiley & Sons, Inc.